Analisis Penyusunan Laporan Keuangan Berdasarkan Sak EMKM: Studi Kasus: UMKM Bumbu Rujak Manis Cak Mimin Surabaya - Musriyah; Anita Carolina (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
MSME Rujak Manis Bumbu Cak Mimin is one of the MSMEs operating in the food sector located in the city of Surabaya and already has a simple financial report, but at this time the financial report needs to be re-examined whether it is in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities. Intermediate (SAK EMKM). This research aims to analyze the process of preparing financial reports for Micro, Small and Medium Enterprises (MSMEs) Bumbu Rujak Manis Cak Mimin based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The research method used is qualitative with a case study approach. Data was obtained through in-depth interviews with business owners and direct observation of the process of consistently preparing their financial reports. Based on data analysis, the research results show that Cak Mimin's Sweet Rujak Bumbu MSMEs have not fully recorded their finances based on the Financial Accounting Standards for Micro, Small and Medium Entities. This is due to a lack of understanding and knowledge regarding Financial Accounting Standards from both workers and business owners.